Principals' Strategies in Improving Student Achievement: A Multi-Site Study - Nisa’, Hasyisyatun Nurun; Padil, Moh.; Barizi, Ahmad (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Improving student achievement is a complex challenge that requires an adaptive leadership approach, especially in educational institutions with different environmental and curricular characteristics. This phenomenon demands a profound understanding of how instructional leadership strategies are effectively implemented in the field. Therefore, this study aims to analyze and compare the principals' strategies in improving student achievement in two educational institutions with different characteristics: Madrasah Ibtidaiyah (MI) IMAMI Kepanjen and Elementary School 4 Panggungrejo. This study used a qualitative approach with a multi-site study design. Data was collected through in-depth interviews, participant observation, and documentation studies to obtain a comprehensive picture of the policies and program implementation in both locations. The findings indicate that at MI IMAMI, the strategy focused on six integrated approaches: developing collaborative programs based on the Independent Curriculum, improving teacher quality through academic supervision, systematic learning evaluation, providing adequate facilities, developing interests and talents, and intensive communication with parents. Meanwhile, at Elementary School 4 Panggungrejo, the strategy emphasized integrated program planning, improving teaching staff competencies, supplementary and remedial programs, strategic partnerships, and a comprehensive reward system. The results of this study indicate that a contextual approach and strong instructional leadership are key to successfully improving student achievement across multiple dimensions. This study provides theoretical and practical contributions regarding the importance of adapting leadership strategies that are responsive to institutional characteristics and the specific needs of students at the elementary school level.